The 8th International Electronic Conference on Sensors and Applications 2021
DOI: 10.3390/ecsa-8-11292
|View full text |Cite
|
Sign up to set email alerts
|

Starter Kit for Electrochemical Sensors Based on Polythiophene Thin Films—Synthesis of High-Quality Films and Protocol for Fast and Gentle Electrode Regeneration

Abstract: Due to their unique properties, polythiophene and other conductive polymers have become the subject of intensive research and are promising substrate materials for innovative and trendsetting applications. To this day, boron trifluoride diethyl etherate (BFEE) is the preferred solvent for the electropolymerization of thiophene, although it does not allow for reproducible film qualities due to its decomposition under ambient conditions. We therefore want to equip the reader with a starter kit for the electropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The configuration of this structure can be seen visually and might provide information about the microscopic organization (24) . Such smooth film surfaces reduce the steric hindrance of eventually immobilized bioreceptors and as a result, could lead to enhanced target sensitivity (18) . Moreover, morphological modifications in the PVA-PTh films illustrated in Figure 3b, were observed when they were coated on stainless steel plates under both control and γ-irradiated environments.…”
Section: Sem Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The configuration of this structure can be seen visually and might provide information about the microscopic organization (24) . Such smooth film surfaces reduce the steric hindrance of eventually immobilized bioreceptors and as a result, could lead to enhanced target sensitivity (18) . Moreover, morphological modifications in the PVA-PTh films illustrated in Figure 3b, were observed when they were coated on stainless steel plates under both control and γ-irradiated environments.…”
Section: Sem Analysismentioning
confidence: 99%
“…Within the spectrum region of 400 to 4000 cm -1 , the spectra were extensively examined, shedding light on the chemical composition and bonding characteristics of these materials. The Table 1 shows the peak positions associated with various major chemical bonds, as given in references (18,19,24) .…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is of utmost importance to carefully dry the working solution since even minor amounts of water negatively affect electropolymerization to the point where film formation can be inhibited completely. We have found that drying the solution of hygroscopic counter ion and solvent over a molecular sieve for at least a week constitutes a simple yet effective method to remove water and allow for successful electropolymerization [18]. This way, we could obtain polythiophene films with exceptionally low charge transfer resistance R CT , which characterizes film conductivity in perpendicular direction and can be obtained from electrochemical impedance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%